2015
DOI: 10.3233/jad-142106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Imprinted Genes is Associated with Risk of Late-Onset Alzheimer's Disease

Abstract: Epigenetic changes including genomic imprinting may affect risk of late-onset Alzheimer’s disease (LOAD). There are >100 known imprinted genes and most of them are expressed in human brain. In this study, we examined the association of single nucleotide polymorphisms (SNPs) in 93 imprinted genes with LOAD risk in 1291 LOAD cases and 958 cognitively normal controls. We performed single-site, gene-based and haplotype analyses. Single-site analysis showed 14 significant associations at P<0.01. The most significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…differentiation could replace lost or damaged neurons that result from Ab plaque and is therefore helpful for improving cognitive dysfunction by establishing new synaptic connectivity (46). Of interest, GPR1 in the brain is a candidate marker for AD as suggested by a gene-based analysis (47). As it is maternally imprinted, GPR1 may provide a mechanism for the higher maternal inheritance in patients with AD (48); therefore, FAM19A1 and its receptor, GPR1, might be associated with neural disorders and neurodegenerative diseases by modulating the functions of NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…differentiation could replace lost or damaged neurons that result from Ab plaque and is therefore helpful for improving cognitive dysfunction by establishing new synaptic connectivity (46). Of interest, GPR1 in the brain is a candidate marker for AD as suggested by a gene-based analysis (47). As it is maternally imprinted, GPR1 may provide a mechanism for the higher maternal inheritance in patients with AD (48); therefore, FAM19A1 and its receptor, GPR1, might be associated with neural disorders and neurodegenerative diseases by modulating the functions of NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…We note that at least seven of our nutrition-sensitive G1 DMRs are in close spatial proximity to imprinted genes, including: IGF1R insulin growth factor1 receptor 1 (53); KCNQ1DN and WT1 important for Wilms tumor biology (54) and ( WT1 ) implicated in neurodegenerative disease(55); the MEST and MESTIT1 genes as maternal stress-sensitive genes regulating parental behaviors and body mass in offspring(56); and SLC22A18AS and VTRNA2-1 which have not yet been explored in the nervous system. Such epigenetic dysregulation—with an impressive >40-fold overrepresentation of methyl-CpG changes for imprinted loci in the present study— could affect not only the risk exposed G1 subjects but also the earliest stages of development in their offspring, even in the absence of an intergenerational transmission of the G1-specific DNA methylation changes.…”
Section: Discussionmentioning
confidence: 99%
“…The Dlgap2 -/- mice have reduced spine density in the orbitofrontal cortex accompanied with downregulation of synaptic proteins, Homer1 and αCaMKII, as well as receptors, NR1 and GluR1, and exhibit exacerbated aggressive behaviors (Jiang-Xie et al, 2014). Molecular and genetic studies have demonstrated that alterations in DLGAP2 are involved the pathophysiology of various psychiatric conditions, including schizophrenia, Alzheimer’s disease, post-tramautic syndrome, and pediatric obsessive-compulsive disorder (Chertkow-Deutsher et al, 2010; Wu et al, 2013; Li et al, 2014b; Chaudhry et al, 2015). Rare de novo CNVs, deletions, and duplications of DLGAP2 have been reported in individuals with ASD, but how mutations of DLGAP2 contribute to autism is still largely unknown (Marshall et al, 2008; Ozgen et al, 2009; Chien et al, 2010; Pinto et al, 2010; Cukier et al, 2014).…”
Section: Synaptic Proteins Regulate Synaptic Function To Maintain Neumentioning
confidence: 99%